using the quadratic formula solve: x(square)-4ax+4a(square)-b(square)

Asked by Harshita Bhola | 12th Nov, 2010, 12:00: AM

Expert Answer:

Dear Student,

The quadratic formula says that:

If there is a quadratic equation rx2 + px + q; then

x = [-p ± √(p2 – 4rq)]/(2r)

Hence,

x2 + 4ax + 4a2 – b

=> x = [-4a ± √{(4a)2 – 4 × 1 × (4a2 – b)}]/2

=> x = [-4a ± 2√b]/2

=> x = -2a ± √b

Regards Topperlearning.

Answered by  | 14th Nov, 2010, 03:55: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.